Adaptive FEM and a posteriori error control for stationary coupled bulk‐surface PDEs. Issue 1 (25th October 2016) - Eigel, Martin; Müller, Rüdiger
Abstract: We consider a system of two coupled elliptic equations, one defined on a bulk domain and the other one on the boundary surface. The numerical error of the finite element solution can be controlled by a residual a posteriori error estimator which takes into account the approximation errors due to the discretisation in space as well as the polyhedral approximation of the surface. The estimators naturally lead to refinement indicators for an adaptive algorithm to control the overall error. Numerical experiments illustrate the performance of the a posteriori error estimator and the adaptive algorithm. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)